Comprehensive analysis, immune, and cordycepin regulation for SOX9 expression in pan-cancers and the matched healthy tissues - Liu, Shuguang; Yang, Lisha; Fu, Jiewen; Li, Ting; Zhou, Baixu; Wang, Kai; Wei, Chunli; Fu, Junjiang (Frontiers in Immunology, 2023)
SRY-box transcription factor 9 (SOX9) is a transcription factor. The SOX9 expression in pan-cancers and the regulation by small molecules in cancer cell lines are unclear. In the current study, we comprehensively analyzed SOX9 expression in normal tissues, tumor tissues and their matched healthy tissues in pan-cancers. The correlation with immunomodulators and immune cell infiltrations in normal and tumor tissues was performed. Cordycepin (CD), an adenosine analog, for SOX9 expression regulation was also conducted in cancer cells. The results found that SOX9 protein is expressed in a variety of organs including high expression in 13 organs and no expression only in 2 organs; in 44 tissues there was a high expression in 31 tissues, medium expression in 4 tissues, low expression in 2 tissues, no expression in other 7 tissues. In pan-cancers with 33 cancer types, SOX9 expression was significantly increased in fifteen cancers including CESC, COAD, ESCA, GBM, KIRP, LGG, LIHC, LUSC, OV, PAAD, READ, STAD, THYM, UCES, and UCS; but significantly decreased only in two cancers (SKCM and TGCT) compared with the matched healthy tissues. It suggests that SOX9 expression is upregulated in the most cancer types (15/33) as a proto-oncogene. The fact that the decrease of SOX9 expression in SKCM and the increase of SOX9 in the cell lines of melanoma inhibit tumorigenicity in both mice and human ex vivo models, demonstrating that SOX9 could also be a tumor suppressor. Further analyzing the prognostic values for SOX9 expression in cancer individuals revealed that OS is long in ACC and short in LGG, CESC, and THYM, suggesting that high SOX9 expression is positively correlated with the worse OS in LGG, CESC, and THYM, which could be used as a prognostic maker. In addition, CD inhibited the both protein and mRNA expressions of SOX9 in a dose-dependent manner in 22RV1, PC3, and H1975 cells, indicating CD’s anticancer roles likely via SOX9 inhibition. Moreover, SOX9 might play an important role in tumor genesis and development by participating in immune infiltration. Altogether, SOX9 could be a biomarker of diagnostics and prognostics for pan-cancers and an emerging target for anticancer drugs’ development.